2001
DOI: 10.1093/embo-reports/kve177
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular signal regulated kinase 5 (ERK5) is required for the differentiation of muscle cells

Abstract: Extracellular signal regulated kinase 5 (ERK5) is a novel member of the mitogen-activated protein kinase (MAPK) family with a poorly defined physiological function. Since ERK5 and its upstream activator MEK5 are abundant in skeletal muscle we examined a function of the cascade during muscle differentiation. We show that ERK5 is activated upon induction of differentiation in mouse myoblasts and that selective activation of the pathway results in promoter activation of differentiation-specific genes. Moreover, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 23 publications
2
77
2
Order By: Relevance
“…We and others have observed that ERK5 is active during the differentiation of C2C12 myoblasts into myotubes (36). ERK2 activity is also elevated during the end stages of differentiation (37,38).…”
Section: Resultsmentioning
confidence: 54%
“…We and others have observed that ERK5 is active during the differentiation of C2C12 myoblasts into myotubes (36). ERK2 activity is also elevated during the end stages of differentiation (37,38).…”
Section: Resultsmentioning
confidence: 54%
“…An expression vector for human KLF4 was purchased from Origene and subcloned by EcoRI digest into pBabe puro. pEGZ expression vectors for wild-type human FLAG-Erk5 and dominant-negative flag-Erk5-AEF have been described before (17). For retroviral expression of small hairpin RNA (shRNA) against Erk5, a 64-mer DNA oligonucleotide containing the specific 19-mer targeting sequence GAGTCACCTGATGTCAACC for human and mouse Erk5 was cloned into the BamHI/HindIII sites of the pRetro Super puro (pRS) shRNA expression vector (18).…”
Section: Methodsmentioning
confidence: 99%
“…7A-D). Activation of ERK5 has been previously shown to regulate the differentiation of myoblasts (Dinev et al, 2001), by regulating the pro-myogenic actions of IGF-2 (insulin-like growth factor 2) (Carter et al, 2009), suggesting that ERK5 regulates the differentiation of a number of cell types.…”
Section: Discussionmentioning
confidence: 99%